Hoax Versus Freedom Of Speech (In The Perspective Of Pancasila) - Riana Susmayanti (Jurnal Supremasi, 2021)
HOAX is a negative consequence of the abuse of freedom of speech. The freedom of speech as part of the citizens' constitutional rights should be exercised responsibly. However, the Act on Electronic Information and Transaction limits the responsibility for HOAX deployment in articles only. Therefore, researchers want to see HOAX as a violation of the norms and values in Pancasila, because of the position of Pancasila as the source of all sources of law. This normative juridical research analyzes dogmatic, theory and legal philosophy which shows that HOAX has violated the norms in the five Precepts of Pancasila.